SMALL RURAL LOCAL GOVERNMENT’S PERFORMANCE FOR THE SOCIAL WORK IN ESTONIA - Raudava, Vaike (European Scientific Journal, ESJ, 2013)
We have observed the four basic functions of the local government level in the context of contemporary social work which aims to empower an individual in the best possible way the person considers appropriate. There are several obstacles preventing the local government from being able to fulfil its duties. At the same time many actual risk groups remain out of the scope of the support system at all. The actions organized by the local government do not empower the individuals in their independent action in the society. The decision-making process follows the principle of collegiality and unfortunately, we can say, the decisions at the client level turn out to be politicised. The unclear situation and big differences in local government level continue because there is no control whatsoever over their activities and no evaluation of their methods from the point of view of social work.